The Digital Sphere as a New Arena for Freedom of Expression: Challenges in Protecting Digital Rights in Indonesia - Alparizi, Parid; Badruzzaman, Muhammad Ziddan; Nugraha, Novan Sya’ban; Adiputra, Rizki Muharamsyah (Candidate: Jurnal Sains Politik, 2025)
The development of digital space has brought fundamental changes to the practice of freedom of expression in Indonesia, while also presenting new challenges in protecting the digital rights of citizens. This study aims to analyze how the digital space functions as an arena for freedom of expression and to identify the dynamics, paradoxes, and challenges of digital rights protection in the context of Indonesia's digital democracy. Using a qualitative approach based on media studies, this study examines digital media texts, policy documents, and public discourse related to online expression, digital regulation, and personal data protection. The analysis was conducted through thematic analysis and critical discourse analysis to reveal the power relations between the state, digital platforms, and society in framing freedom of expression. The results of the study show that digital space opens up vast opportunities for public participation, social control, and democratization of information, but at the same time is faced with the criminalization of expression, ambiguous regulations, and weak data security and privacy guarantees. The tension between efforts to control information and protect human rights places freedom of expression in a vulnerable position. This study concludes that strengthening digital democracy in Indonesia requires fair regulatory reform, transparency in platform moderation policies, and increased digital literacy among the public so that digital space can develop as a safe, inclusive, and democratic public space.